Comparison of Peroperative Peritonsillar Injection of Adrenaline vs Control to Reduce Intraoperative Bleeding in Tonsillectomy Patients - Momina Zeb, Asad Ullah, Sadaf Raffat Mustafa, Wajih-Ud-Din Shinwari, Mehreen Babar, Minahil ArshadMomina Zeb, Asad Ullah, Sadaf Raffat Mustafa, Wajih-Ud-Din Shinwari, Mehreen Babar, Minahil Arshad, (Pakistan Journal of Medical & Health Sciences, 2024)
Background: Tonsillectomy is a common surgical procedure that is being carried out in ENT departments. Tonsillar enlargement can lead to airway obstruction, disrupts normal sleep patterns and can cause dysphagia. This procedure is frequently associated with significant intraoperative and postoperative bleeding. Therefore various methods and techniques have being used to reduce both intraoperative and postoperative bleeding. Objective: To determine the effectiveness of preoperative peritonsillar injection of adrenaline to reduce intraoperative bleeding in tonsillectomy patients. Study design: Quantitative randomized controlled trial. Place and duration of study: Department of Otorhinolaryngology and Head and Neck Surgery, PIMS, Islamabad from 1st August 2022 to 31st January 2023. Methodology: Ninety eight patients with clinical and demographic data, undergoing tonsillectomy were enrolled. After proper history and examination, patients were divided into two groups; group A (received adrenaline prior to tonsillectomy) and group B (control group). Peroperative blood loss in both the groups during surgery was estimated on the basis of quantity of blood in the suction machine and number of blood soaked sponges .Effect of adrenaline on the time to achieve hemostasis number of cauterization and operation duration was also studied. Results: There was marked reduction in the amount of blood loss in group A than group B that was statistically significant. There was mild reduction in the time to achieve hemostasis, number of cauterization used and duration of surgery that was also statistically significant (P<0.005). Conclusion: A marked reduction in peroperative loss of blood, total time required for surgery, number of cautery used was observed in the study group. Keywords: Tonsillectomy, Peroperative bleeding, Adrenaline.